SARS-CoV-2 virus in raw wastewater from student residence halls with concomitant 16S rRNA bacterial community structure changes - Li, Ye; Ash, Kurt T.; Joyner, Dominique; Williams, Daniel E.; Hazen, Terry C. (Frontiers in Microbiology, 2025)
The detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA in sewage is well-established, but the concomitant changes in microbial compositions during the pandemic remain insufficiently explored. This study investigates the impact of the SARS-CoV-2 virus on microbial compositions in raw sewage, utilizing high-throughput 16S rRNA amplicon sequencing to analyze wastewater samples collected from six dormitories over a one-year field trial at the University of Tennessee, Knoxville. The concentration of SARS-CoV-2 RNA was assessed using a reverse transcription-quantitative polymerase chain reaction. Significant variations in bacterial composition were evident across the six dormitories, highlighting the importance of independently considering spatial differences when evaluating the raw wastewater microbiome. Positive samples for SARS-CoV-2 exhibited a prominent representation of exclusive species across all dormitories, coupled with significantly reduced bacterial diversity compared to negative samples. The correlation observed between the relative abundance of enteric pathogens and potential pathogens at sampling sites introduces a significant dimension to our understanding of COVID-19, especially the notable correlation observed in positive SARS-CoV-2 samples. Furthermore, the significant correlation in the relative abundance of potential pathogens between positive and negative SARS-CoV-2 raw sewage samples may be linked to the enduring effects of microbial dysbiosis observed during COVID-19 recovery. These findings provide valuable insights into the microbial dynamics in raw sewage during the COVID-19 pandemic.